Respuesta :

Answer:

Step-by-step explanation:

First of all, you have to set up the equation

2x^2 + x -1 = 2               Subtract 2 from both sides

2x^2 + x - 1 - 2 = -2+2   Combine

2x^2 + x - 3 = 0             This factors.

(2x + 3)(x -1 ) = 0

Either

2x + 3 = 0                       Subtract 3 from both sides

2x = - 3                           Divide by 2

2x/2 = - 3/2                    

x = - 3/2                         which you already know

or

x - 1 = 0                          Add 1

x - 1 + 1 = 1

x = 1

the other answer is x = 1